AuNPs@MIL-101 (Cr) as a SERS-Active Substrate for Sensitive Detection of VOCs - Xie, Dan; Wang, Ruimeng; Fu, Jinghao; Zhao, Zhongxing; Li, Min (Frontiers in Bioengineering and Biotechnology, 2022)
Surface enhanced Raman scattering (SERS) is an important and powerful analytical technique in chemical and biochemical analysis. Metal organic frameworks (MOFs) are suitable for the study of catalysis, separation, gas storage, biomedical applications, and proton conduction. MOFs can effectively capture volatile organic compounds (VOCs) with high adsorption capacity and fast kinetics, and the local surface plasmon resonance characteristics of gold nanoparticles can quickly and effectively distinguish different VOCs by SERS. Combining both, we designed a novel SERS substrate based on embedding gold nanoparticles (AuNPs) within MIL-101(Cr) for recognition of various VOC in the gaseous phase. This work provides a new way for sensitive detection of VOCs at ppm-level. The occupying of AuNPs inside MIL-101(Cr) increases the micropores specific surface area of AuNPs@MIL-101(Cr), which enables AuNPs@MIL-101(Cr) absorb more toluene molecules and consequently realizes its high detection sensitivity. The detection limit of toluene, 4-ethylbenzaldehyde, and formaldehyde is decreased to 6, 5, 75 ppm respectively. Moreover, this substrate can be used for detecting different VOCs simultaneously. Finally, we discussed the enhancement of AuNPs outside and inside MIL-101(Cr) on the Raman signal.